The Descriptive Study On Tie Grammatical Deviation of Nonstandard English Found in Huckleberry Finn - Aris Widiyono (Faculty of Letters, 2002)
The daily language that we use for any ultimate goal of communication is not a single undivided one (Strevens, 1972:8). Likewise the various color of human skin, a language can be divided into several types of varieties. This is not only obviously seen between the two separate languages, but also found within a language shared in common In particular we may speak a language in a way differently from our acquaintances. It makes sense since it is the nature of every living language to have more than one variety especially when it is spoken or in the form of speech. Whatever language it is, even a language with a limited number of pcople who live in a small area for their own local needs is certain to have varieties, It becomes greater on a language with big amount of speakers who spread over a large geographical arca for a wide range of local, national, and international aflairs. At any rate, English has maintained the later typc of language that possesses a large number of varietics.
Reupload file repository 7 April 2026_Rudy/Halima
Keywords: Grammatical Deviation; Huckleberry Finn